Prevalence of severe childhood obesity in England: 2006–2013. Issue 7 (27th January 2015) - Ells, Louisa J; Hancock, Caroline; Copley, Vicky R; Mead, Emma; Dinsdale, Hywell; Kinra, Sanjay; Viner, Russell M; Rutter, Harry
Abstract : Background: International evidence shows that severe paediatric obesity results in an increased risk of ill health and may require specialised weight management strategies, yet there remains a lack of data on the extent of the problem. Objective: To examine the prevalence of severe obesity in children aged 4–5 and 10–11 years, attending English schools between 2006/2007 and 2012/2013. Design: A retrospective analysis of National Child Measurement Programme (NCMP) data. Setting: Maintained schools in England. Participants: All children aged 4–5 and 10–11 years included in the NCMP dataset. Main outcome measures: Prevalence of severe childhood obesity, defined using the 99.6th centile of the British 1990 (UK90) growth reference for body mass index (BMI), analysed by sex, geography, ethnic group and deprivation. Results: The key findings show that in 2012/2013, severe obesity (BMI ≥UK90 99.6th centile) was found in 1.9% of girls and 2.3% of boys aged 4–5 years, and 2.9% of girls and 3.9% of boys aged 10–11 years. Severe obesity prevalence varies geographically and is more prevalent in children from deprived areas, and among those from black ethnic groups. Conclusions: The findings from this study should help to raise awareness of the prevalence of severe obesity and support the provision of adequate treatment and prevention services both to support children who are already severely obese and reduce the prevalence of extreme weight in the future.